2015
DOI: 10.1186/s12911-015-0182-2
|View full text |Cite
|
Sign up to set email alerts
|

Tailored e-Health services for the dementia care setting: a pilot study of ‘eHealthMonitor’

Abstract: BackgroundThe European eHealthMonitor project (eHM) developed a user-sensitive and interactive web portal for dementia care: the eHM Dementia Portal (eHM-DP). It aims to provide targeted and personalized support for informal caregivers of people with dementia in a home-based care setting. The objective of the pilot study was to obtain feedback on the eHM-DP from two user perspectives (caregivers and medical professionals), focusing on caregiver empowerment, decision aid, and the perceived benefits of the eHM-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 36 publications
1
48
0
5
Order By: Relevance
“…However, concerning case studies, all conducted evaluation at the end of the intervention. Although several aspects of evaluation have been found in conceptual articles [32][33][34][35][36][37][38][39]41], the case studies mostly evaluated clinical [20,[42][43][44][46][47][48][49][52][53]55,[59][60][61][64][65], and human/social aspects [42,[46][47][48][49][53][54][55]59,61,63,65].…”
Section: Discussionmentioning
confidence: 99%
“…However, concerning case studies, all conducted evaluation at the end of the intervention. Although several aspects of evaluation have been found in conceptual articles [32][33][34][35][36][37][38][39]41], the case studies mostly evaluated clinical [20,[42][43][44][46][47][48][49][52][53]55,[59][60][61][64][65], and human/social aspects [42,[46][47][48][49][53][54][55]59,61,63,65].…”
Section: Discussionmentioning
confidence: 99%
“…research has focused on one or a few of the SDM elements and not on the complete process. Articles in the review focused, by way of differing PHR architectural and functional designs, on such topics as the provision of alerts for the identification of a decision-making opportunity [36], patient access to health information and educational resources to support informed decision-making [50], provision of decision support tools to aid the patient with informed choice[ [22], [38], [45], or varying communications functionality to support online patient-provider interactions for decision-making [53].…”
Section: Sdm Via Phr Gapmentioning
confidence: 99%
“…One article specifically identified the relevance of personalizing decision support and action planning with a combination of the patient medical profile, preferences and goals, and provider recommendations [27]; however, in common with the few other articles that identified the importance of patient preferences to guide action, previously collected patient preferences are often used to guide the decision making rather than an elicitation of preferences in context of all factors for the decision at hand, at that point in time. While the inclusion of decision aids in PHRs to support patients with decisions by weighing the benefits, harms and scientific uncertainties improve outcomes [38], [47], its use has been limited and varied, and depends on the complexity and intelligence of the integrated decision support system [22], [23]. Computer tailoring a decision aid based on the patient clinical profile and clinical practice guidelines, and delivered in a meaningful way to explain outcomes and probabilities to patients has proved challenging and hence the computerized, generic paper form was often the default [23]; yet, decision-support services in the form of context specific decision aids are the future of decision making [49].…”
Section: Summary: Thematic Analysis -Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a tool that had been shown to be feasible for professionals was offered to patients without making many adjustments. Other studies show that modifying language is not necessary 10 , 35. The benefits of having information surmount language problems; however, tailoring of content is recommendable.…”
Section: Discussionmentioning
confidence: 99%